THE ROLE OF COMMUNITY IN WOMEN'S EMPOWERMENT (Study on the South Tangerang Regional MoM Academy Community) - Rahajeng Pusitosari; Anita Permata Sari (RADJA PUBLIKA, 2026)
This study aims to analyze the role of community in women’s empowerment within the MoM Academy Regional South Tangerang community. Women in modern society continue to face various social, psychological, and economic challenges that influence their self-development and participation in social life. In this context, women-based communities play an important role in providing social support, self-development opportunities, and empowerment spaces for women. This study employed a qualitative approach with a descriptive method and a constructivist paradigm. Data were collected through in-depth interviews, participatory observation, and documentation studies involving community leaders, administrators, and active members of MoM Academy Regional South Tangerang selected through purposive sampling. The findings reveal that the community functions not only as a social gathering space but also as a medium for women’s empowerment through digital training, public speaking, entrepreneurship, and self-development activities. The community successfully builds a strong sense of belonging, emotional support, and interpersonal communication among members. Furthermore, the community contributes positively to increasing women’s self-confidence, communication skills, digital competencies, social participation, and economic independence. Women who were previously limited to domestic activities became more confident in expressing opinions, participating in social activities, and generating additional income through digital-based activities and home businesses. The study concludes that MoM Academy Regional South Tangerang plays a significant role as a social support system and agent of social change in strengthening women’s empowerment socially, psychologically, and economically. The existence of supportive women’s communities is essential in creating inclusive social spaces that encourage women to become more independent, confident, and productive in modern society.